SMA foil-based elastocaloric cooling: from material behavior to device engineering. (22nd September 2017) - Bruederlin, F; Ossmer, H; Wendler, F; Miyazaki, S; Kohl, M
Abstract: The elastocaloric effect associated with the stress-induced first order phase transformation in pseudoelastic shape memory alloy (SMA) films and foils is of special interest for cooling applications on a miniature scale enabling fast heat transfer and high cycling frequencies as well as tunable transformation temperatures. The focus is on TiNi-based materials having the potential to meet the various challenges associated with elastocaloric cooling including large adiabatic temperature change and ultra-low fatigue. The evolution of strain and temperature bands during tensile load cycling is investigated with respect to strain and strain-rate by in situ digital image correlation and infrared thermography with a spatial resolution in the order of 25 µ m. Major design issues and challenges in fabrication of SMA film-based elastocaloric cooling devices are discussed including the efficiency of heat transfer as well as force recovery to enhance the coefficient of performance (COP) on the system level. Advanced demonstrators show a temperature span of 13 °C after 30 s, while the COP of the overall device reaches almost 10% of Carnot efficiency.